Illocutionary Acts in the Instagram Captions of Taylor Swift's Eras Tour Promotions - Meliana Oktaviani Susilo (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
The study analyzes the use of illocutionary acts in the Taylor Swift’s Eras Tour Instagram captions. It aims to examine the types and patterns of illocutionary acts used in the captions. The writer is interested in understanding the intention behind Swift’s words in the Instagram captions.  In analyzing the data, the writer applied Yule’s classification of illocutionary acts (1996) and employed a qualitative approach. A total of 24 Instagram captions related to the Eras Tour were selected and analyzed. The findings reveal that representative, commissive, and expressive acts were used in the captions. These illocutionary acts allowed Swift to express gratitude, state facts, and make promises. In addition, the writer identified five patterns of illocutionary acts in the captions. The study concludes that Swift uses Instagram captions not only to inform and announce her tour but also to express her feelings and promise to meet her fans.